Attitudes and tolerance of private landowners shape the African wild dog conservation landscape in the greater Kruger National Park - Parker, DM; Watermeyer, JP; Davies-Mostert, HT; Beverley, G; Marnewick, K (Endangered Species Research, 2018)
The survival of wildlife ultimately relies on its acceptability to humans. The African wild dog Lycaon pictus is an endangered species that often comes into conflict with humans. Currently, the only viable population in South Africa resides in the Kruger National Park (KNP). To begin to understand the acceptability of wild dogs outside this important wild dog stronghold, we interviewed private landowners (n = 186) along the KNP western and southern boundaries. Respondents generally held positive attitudes towards wild dogs and had a good knowledge of them. Attitudes were also more positive when the property was part of a conservancy, indicating that the conservation landscape for wild dogs on private land outside the KNP is promising. However, the impact of edge effects such as disease transmission should not be ignored in future research, and creative solutions for mitigating these effects must be sought to ensure the future conservation of wild dogs.